Transgenerational Effects of Maternal Immune Activation on Specific Antibody Responses in Layer Chickens - Verwoolde, Michel B.; Arts, Joop; Jansen, Christine A.; Parmentier, Henk K.; Lammers, Aart (Frontiers in Veterinary Science, 2022)
Activation of the maternal immune system may affect innate and adaptive immune responses in the next generation and may therefore have implications for vaccine efficacy and dietary immune modulation by feed additives. However, transgenerational effects on immune responses in chickens have been investigated to a limited extend. The present study investigated effects of intratracheal (i.t) specific and aspecific immune activation of laying hens on specific antibody production in the next generation. In two experiments laying hens received intratracheally an immune stimulus with human serum albumin (HuSA) or lipopolysaccharide (LPS). In experiment 1, hatchlings of the immune activated hens were at 4 weeks i.t. immunized with HuSA or HuSA+LPS. Maternal immune activation with LPS increased HuSA specific IgG and IgM responses in offspring. These results suggest a transgenerational effect of the maternal immune system on the specific antibody response in the next generation. In experiment 2 hatchlings received either β-glucan-enriched feed or control feed and were i.t. immunized with HuSA. Maternal immune activation with LPS decreased IgG anti-HuSA responses after HuSA immunization within hatchlings that received β-glucan enriched feed. The results of Experiment 2 suggest a transgenerational link between the innate immune system of mother and specific antibody responses in offspring. Despite variabilities in the outcomes of the two experiments, the observations of both suggest a link between the maternal innate immune system and the immune system of the offspring. Furthermore, our results may imply that maternal activation of the innate immune system can influence immune modulating dietary interventions and vaccine strategies in the next generation.